Dispersed gold nanoparticles supported in the pores of flower-like macrocellular siliceous foams based on an ionic liquid as catalysts for reduction. Issue 54 (17th May 2016) - Zhao, Shuo; Zhang, Yiwei; Zhou, Yuming; Zhang, Chao; Sheng, Xiaoli; Fang, Jiasheng; Zhang, Mingyu
Abstract : A facile method has been developed for the synthesis of a flower-like macrocellular siliceous foam with a large and uniform pore size, using P123 and protic ionic liquid as the co-templates under acidic conditions. Abstract : A facile method has been developed for the synthesis of a flower-like macrocellular siliceous foam with a large and uniform pore size, using P123 and protic ionic liquid as the co-templates under acidic conditions. The influence of the protic ionic liquid concentration and the hydrothermal temperature on the synthesis of the macrocellular siliceous foam is systematically investigated. The structures of all the composites were characterized by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), X-ray powder diffraction (XRD), UV-vis diffuse reflection spectroscopy, and N2 gas sorption. The results showed that the flower-like macrocellular siliceous foam possessed about 100 nm sized large pores, which was appropriate for it to be applied in catalytic reactions. Moreover, Au NPs were immobilized in the pores of the flower-like macrocellular siliceous foam through a self-assembly procedure. The obtained NH2 -S-6-393/Au sample exhibited a remarkably higher catalytic activity in the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) by NaBH4 . The macrocellular siliceous foams are suitable supports for catalytic reactions on account of their special structure and can be highly beneficial for a wide range of applications.